Quantitative Based Training Model Ssytem to Enhance Adolescent Performance in Youth Football Academies - Luki Ardiantoro; Sugianto; Arbiati Faizah; Nissa Ayunda (RAM PUBLISHER, 2026)
This inter-institutional collaborative community service initiative aims to transform conventional soccer training models into a structured, sport-science-driven approach at the XYZ Youth Football Academy in Mojokerto. The primary challenges faced by the partner academy include a lack of coaching competencies in designing quantitatively structured training programs, an absence of scientific training methods, and a lack of objective physical evaluation tools. The program was executed through an integrated workflow encompassing program socialization, quantitative periodization workshops, the implementation of Small-Sided Games (SSG), and continuous mentoring on cardiorespiratory endurance evaluations using the Balke Protocol VO₂Max test. A sport science approach was strictly maintained to simultaneously enhance physical, technical, and tactical attributes in young players. The outcomes demonstrated a significant increase in coaching competencies regarding data-driven periodization, consistent execution of adaptive SSG drills, and a statistically verified improvement in the students' aerobic capacity when comparing pre-test and post-test values. In conclusion, reinforcing quantitative sports management through SSG effectively elevates the quality of youth sports coaching into a professional, objective, and sustainable ecosystem